Effect of dienogest on pain and ovarian endometrioma occurrence after laparoscopic resection of uterosacral ligaments with deep infiltrating endometriosis. (September 2017) - Yamanaka, Akiyoshi; Hada, Tomonori; Matsumoto, Tsuyoshi; Kanno, Kiyoshi; Shirane, Akira; Yanai, Shiori; Nakajima, Saori; Ebisawa, Keiko; Ota, Yoshiaki; Andou, Masaaki
Abstract: Objective: To evaluate the effect of dienogest (DNG) in preventing the occurrence of pain and endometriomas after laparoscopic resection of uterosacral ligaments (USLs) with deep infiltrating endometriosis (DIE). Study design: This retrospective analysis included 126 patients who underwent laparoscopic resection of USLs with DIE followed by postoperative administration of DNG or no medication. Every 6 months postoperatively, patients answered questions and underwent ultrasound examination to identify pain and/or endometrioma. Result: There were three (5.0%) cases of endometrioma in 59 patients from the DNG group and 21 (31.3%) cases in 67 patients from the no medication group ( P = 0.0002). Pain returned to preoperative levels in eight (11.9%) cases in the no medication group. No recurrence of pain occurred in the DNG group ( P = 0.0061). Conclusion: The administration of DNG after resection of USLs with DIE significantly reduces the occurrence rate of endometriosis-related pain and endometriomas.